Flowers for Palestine: From Holy City to Holy City - Harris, Tiffany Octavia (Critical Education, 2026)
We are a Black femme-led multidisciplinary group of artists, activists, community members, and most importantly human beings who are committed to creative resistance in solidarity with Palestine. As Black people based in the greater Charleston South Carolina area, we are connected to the legacy of resilience and resistance in the Lowcountry. Our inspiration stems from a feminist, armed resistance group, the Chrysanthemum Flowers, established pre-Nakba in 1933. Emboldened by these eco-radical ancestors, we aimed to create a larger-than-life sized public flower installation to express continued solidarity with the Palestinian liberation movement. This paper documents the nine months preceding our proposed installation which included collaboration with various community groups to lead arts workshops, film-screenings, book discussions, and teach-ins about the intersections of Black and Palestinian liberation, how to build collective power, and several ways to stand with Palestine and other oppressed peoples around the world. This paper outlines our organizing process including: 1) show of solidarity, 2) relationship-building, and 3) sustainable, ongoing practice. Ultimately, we are guided by the Combahee River Collective Statement which calls for action on both local and global issues to strive for coalition building with women of color and persons in the Global South.